The Impact of Antimicrobial Stewardship Program on Injudicious Use of Cefuroxime - Arulappen, Ann L.; Danial, Monica; Haron, Norliza; Hau, Lim Choo; Khan, Amer Hayat (Frontiers in Pharmacology, 2021)
Antimicrobial stewardship (AMS) program promotes the judicious use of antimicrobials. Hence, this study was conducted to analyze the impact of stewardship on the prescribing pattern of cefuroxime injection among the surgeons as perioperative antimicrobial prophylaxis (PAP). This study was conducted retrospectively in Malaysia. Various outcomes were measured including cefuroxime usage, compliance with the guidelines, surgical site infections, and cost savings. A total of 1,601 patients were recruited in the study. In terms of usage, the total defined daily dose (DDD) prior to the intervention was 202 DDD/100 procedures compared to that after intervention which was 144 DDD/100 procedures (p < 0.05). On the other hand, the excessively long administration of PAP dropped from 94.4 to 30.3% (p < 0.001). Focusing on the compliance with the newly developed local guidelines, it has increased from 53 to 94.3% after the interventions were made (p < 0.001), whereas the rate of surgical site infections was reduced from 17.0 to 9.0%. The cost of antibiotic being used has significantly reduced after the study intervention (p = 0.007). The quality of PAP directly impacts the antimicrobial usage, the surgical site infections, and the total cost involved. Thus, it is crucial to maintain the standard of PAP at all times in healthcare settings.